Buth Savong and the New Proliferation of Relics in Cambodia - John Marston (Estudios de Asia y África, 2015)
The article describes the movement in Cambodia surrounding the lay Buddhist leader Buth Savong, who has come to prominence in the country since the 1990s. Among the characteristics of this organization is attention to the spatial organization of the temples and ashrams affiliated with Buth Savong and an emphasis on the installation of Buddha relics. The article explores the movement in the context of Cambodian socio-political change and discusses the implication of this new emphasis on relics, giving three case studies.